Legal Framework of Community-Based Water Resource Management to Achieve SDGs and “No One Left Behind” - Rosita Candrakirana; Affan Akbareldi; Adinda Rizky Fajri; Devica Rully Masrur (Faculty of Law, Universitas Jenderal Soedirman, 2024)
This study aims to examine community-based water resources management implemented in Umbul Ponggok Village, Klaten Regency, Central Java, Indonesia, based on the Water Resources Law (2019) and was subsequently modified by the Job Creation Law (2023), which prioritizes the well-being of the local community and in order to achieve sustainable development goals (SDGs), especially the principle of No.-One Left Behind. Community involvement in water resources management is very important. Therefore, communities no longer only act as consumers but also as those who determine their own needs for water resources. One area that has implemented this approach is the community in Ponggok Village, Klaten Regency. Therefore, this study addressed the compliance of the community-based water resource management in Ponggok Village, Klaten Regency, with the existing regulations. The study also determined whether the community complies with the principles of Sustainable Development Goals (SDGs) through a juridical-empirical method. Data was collected through documentation and interviews, and qualitatively analyzed. The result showed that the practices of water resource management in Ponggok Village aligned with existing regulations. However, a notable gap existed in adhering to reporting regulations, attributed to a lack of awareness among the village apparatus. Then, the water resource management in Ponggok Village has fully aligned with the current regulations and the SDGs' principles.